Numerical study of axisymmetric hybrid nanofluid MgO-Ag/H2O flow with non-uniform heat source/sink - Muhammad Yasir; Masood Khan; A.S. Alqahtani; M.Y. Malik (Alexandria Engineering Journal, 2023)
The physical strength, mechanical resistance, chemical stability, thermal conductivity, and other properties of hybrid nanoparticles are more satisfactory than those of individual nanofluids. The thermal performance of hybrid nanofluids has been the subject of an increasing number of studies in the literature. A significant research is done on theoretical correlations for estimating the thermophysical characteristics of nanofluids. The performance of hybrid nanofluids for heat transmission is investigated in the present work through a comparative analysis. For this, a mathematical model is formulated by considering the impact of thermal radiation and irregular heat source/sink in a porous medium. In this study, the magnetized flow of nanofluid MgO/H2O and hybrid nanofluid MgO-Ag/H2O are studied numerically. The controlling flow model of PDEs is transformed into ODEs by using the similarity transformation. The results revealed that the hybrid nanofluid fluid's thermal conductivity is more effective than the nanofluid's thermal conductivity. Further, the use of high suction strengths higher the heat transfer for both solutions while the opposite trend occurred for friction drag.